Analisis Fungsi Pengawasan DPRD Terhadap Pelaksanaan Anggaran Pendapatan dan Belanja Daerah di Kabupaten Waropen - Niki, Dani Yordan; Ngutra, Risky Novan; Kambuaya, Quincy F. (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2024)
The aim of the research is to analyze the implementation of the Waropen DPRD's supervisory function regarding Waropen APBD Management. To analyze the factors inhibiting the implementation of supervision by the DPRD Wropen regarding the management of the APBD. The analysis methods used are validity tests, reliability tests, and qualitative description analysis methods. From the results of the discussion, it can be concluded: (1). Respondents' perceptions in answering questions related to the variable Implementation of the Supervisory Function of the Regional People's Representative Council by listening to opinions, asking for information, investigating, working visits and accepting aspirations from 20 respondents or (100%) chose very suitable. (2). Respondents' perceptions in answering questions related to the variable Factors Inhibiting the Implementation of Supervision with indicators of knowledge, skills, facilities and infrastructure, participation from 20 respondents or (100%) chose very suitable.